Studies of Anti-Viral Activity of Chemically Synthesized Compounds against Orthopoxviruses in vitro - A. S. Kabanov; Al. A. Sergeev; L. E. Bulychev; N. I. Bormotov; L. N. Shishkina; Ar. A. Sergeev; S. A. Bodnev; M. O. Skarnovich; A. R. Shevtsov; B. A. Selivanov; A. Ya. Tikhonov; A. P. Agafonov; et al. (Проблемы особо опасных инфекций, 2013)
for ST-246 and NIOC-14 is within the range of 0,001-0,004 µg/ml, and IS for both of them is > 100000. In addition, ST-246 and NIOC-14 chemical compound efficacy, concentrated up to 0,0125; 0,025 and 0,05 µg/ml, in accordance with prophylactic charts describing an impact on ectromelia virus (EV) infectivity in vitro, is consequently 0,6; 3 and 1 lg higher than in case of compound application after an hour of Vero cells infection with EV.